Twenty years’ experience of midgut malrotation and volvulus in a tertiary center in northern Taiwan: A retrospective study - Wen-Yu Tseng; Ming-Wei Lai; Jin-Yao Lai; Chien-Chang Chen; Hsun-Chin Chao; Jeng-Chang Chen; Shih-Yen Chen; Yung-Ching Ming; Hung-Yu Yeh; Hung-Hsiang Lai; Sze-Ya Ting; Pai-Jui Yeh (Pediatrics and Neonatology)
Background: Early diagnosis and surgical intervention for midgut malrotation with bowel obstruction are crucial. We aimed to identify risk factors for adverse outcomes in infants with midgut malrotation and to develop a prediction model. Methods: We reviewed the operation records of infants surgically diagnosed with midgut malrotation at Chang Gung Children's Medical Center between January 2000 and December 2020. Patients were classified into the poor-outcome group (PO) if they underwent bowel resection or experienced mortality; all others were categorized as the favorable-outcome group (FO). Data on demographics, initial presentations, laboratory results, radiographic or sonographic findings, maternal conditions, and outcomes were collected and analyzed. Fisher's exact test, the independent sample t-test, and the Mann-Whitney test were utilized for comparative analysis when suitable. Results: The study included 103 infants. Eleven were in the PO group, and 92 were in the FO group. Initial presentations such as respiratory distress, poor activity, and shock status were notably more prevalent in the PO group. The INR, hemoglobin, HCO3, base excess, and aspartate transaminase values showed significant variation between the two groups. Multivariate analysis identified that lower hemoglobin (OR 0.677, p = 0.043) and higher AST (OR 1.036, p = 0.044) were independent predictors of adverse outcomes. An AST/Hb ratio of <3.78 demonstrated a high negative predictive value (98.6%) for an adverse outcome in midgut malrotation. Conclusions: Prompt diagnosis and surgical treatment of midgut malrotation are vital to prevent bowel resection or mortality. The independent predicting factors for poor outcomes include low hemoglobin and elevated AST levels.